Diethylene glycol poisoning in Gurgaon, India, 1998 - Singh Jagvir; Dutta A.K; Khare Shashi; Dubey N.K; Harit A.K; Jain N.K; Wadhwa T.C; Gupta S.R; Dhariwal A.C; Jain D.C; Bhatia Rajesh; Sokhey Jotna (The World Health Organization, 2001)
OBJECTIVE: To discover the cause of acute renal failure in 36 children aged 2 months to 6 years who were admitted to two hospitals in Delhi between 1 April and 9 June 1998. METHODS: Data were collected from hospital records, parents and doctors of the patients, and district health officials. Further information was obtained from house visits and community surveys; blood and stool samples were collected from other ill children, healthy family members and community contacts. Samples of drinking-water and water from a tube-well were tested for coliform organisms. FINDINGS: Most of the children (26/36) were from the Gurgaon district in Haryana or had visited Gurgaon town for treatment of a minor illness. Acute renal failure developed after an episode of acute febrile illness with or without watery diarrhoea or mild respiratory symptoms for which the children had been treated with unknown medicines by private medical practitioners. On admission to hospital the children were not dehydrated. Median blood urea concentration was 150 mg/dl (range 79-311 mg/dl) and median serum creatinine concentration was 5.6 mg/dl (range 2.6-10.8 mg/dl). Kidney biopsy showed acute tubular necrosis. Thirty-three children were known to have died despite being treated with peritoneal dialysis and supportive therapy. CONCLUSION: Cough expectorant manufactured by a company in Gurgaon was found to be contaminated with diethylene glycol (17.5%v/v), but a sample of acetaminophen manufactured by the same company tested negative for contamination when gas-liquid chromatography was used. Thus, poisoning with diethylene glycol seems to be the cause of acute renal failure in these children.